Sejarah Perkembangan Islam di Desa Josari (Studi Kasus Masjid Darul Muttaqin) - Iis Uun Fardiana (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2018)
The existence of Islam in Indonesia as a proven teaching with the Pondok Pesantren as a place of spread of Islam. However, the history of the Muslims inPonorogo is not widely known by a wide audience, as if the Islamic civilization in Ponorogo has no effect on the historical development of a nation. Thereforethe authors do this penilitian to know the history of the Mosque Daarul Muttaqien in Josari Village, and the history of the building Mosque DaarulMuttaqien in Josari Village. This study uses historical method. The results showed that in the mid 17th century Islam began to enter in the village ofJosari. The person who brought Islam in Josari Village came from Jepara named Imam Ash‟ari who is a student of Kyai Donopuro Dukuh SetonoTegalsari Village. Provided by Imam Ash‟ari mosque sent by Kyai Donopuro mengsyiarkan Islam in the village of Josari, because at that time still Hindu. Insyiarnya he founded Pondok Pesantren. Mosque Daarul Muttaqien is a very sturdy mosque building. The wood used to build the mosque Daarul Muttaqienis teak wood, which is obtained from the jungle precisely in Demangan Village. And finally stood the mosque Jami „Josari (Darul Muttaqien), when viewed interms of building much influenced by Hindu - Javanese culture. Which aims to attract the Hindu community to embrace Islam.